Mineralogy, Trace Elements, and Rare Earth Element Composition of Sediments in an Amazonian Whitewater River: The Acre River - Duarte, Alejandro; Dionisio Calderon, Enrique Roy; de Avillez, Roberto R.; Siciliano, Bruno; Gioda, Adriana (Journal of Environmental Science and Engineering Technology, 2025)
This study characterizes the mineralogical and geochemical composition of suspended (SS) and riverbed sediments (BS) from the Acre River, a whitewater tributary in Southwestern Amazonia. Four SS and four BS samples collected during the dry season were homogenized into composite samples and analyzed by different analytical techniques (ICP-MS, ICP OES, XRD, and FTIR). The results showed that quartz (up to 75 %) and kaolinite (up to 38 %) were the dominant minerals, together with feldspars and TiO2. Rare earth elements (REEs) were present at low to moderate concentrations (0.11-52 µg g-1), with Ce and La being the most abundant. Trace elements such as V, Ni, Ga, Rb, and Cs showed enrichment relative to upper continental crust. Although the single-season sampling limits temporal interpretation, comparison with published datasets from the Purus and Solimões basins suggests that both natural weathering and local land-use pressures influence sediment composition. These results provide new geochemical data for a poorly studied Amazonian tributary and contribute to the broader understanding of sediment provenance and hydrogeochemical processes in whitewater rivers.